Ethics and semantics - Lombardi, Maria (Medicina e Morale, 1990)
A rich terminology is used today (in Italian) in order to define the nature of the operations on embryos. In most instances implicit connotations and anthropological presuppositions are hidden. The first part shows that terms from genetic manipulation or engineering up to "procreatics", far from being objective scientific descriptions, aim in fact to suggest a positive evaluation, disregarding human and social problems linked with such operations. The second part analyses the notional gap between the biological features of the embryo and the quality of person which must be ascribed to it on philosophic grounds. Within a linguistic approach, the article leads to the conclusion that the multiplicity of terms is a positive and fertile mark of the still living consciousness that a human embryo may never be reduced to a mere object of technology.